Borrowed Words of Non-Slavic and Slavic Origin in Sixteenth-Century Standard Slovenian - Andreja Legan Ravnikar (Jezikoslovni zapiski, 2015)
A lack of expressions represents the strongest motivation for borrowing words from the inventory of other languages into sixteenth-century standard Slovenian. A comparison among writers, primarily between Trubar and Dalmatin versus Krelj and Juričič, with regard to distinguishing linguistic concepts and sociolinguistic circumstances reveals a differing share of words in their works borrowed from German, classical languages and Biblical languages, Romance languages, and Slavic languages. This article analyzes the semantic character or semantic development of more recent and older borrowed words.